MODERNITY AND THE VERNACULAR - Schaber, Bennet (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1991)
The vernacular in medieval literature, jazz, and rock and roll, as an avant-garde practice, a search for a sociality in the absence of pre-existing rules. Contrast between modernist experimentation (which is teleological and project-oriented) and the vernacular encounter with sheer chance. The social poetics of the vernacular as a way of rethinking the relation between literature and society.